PENINGKATAN HASIL BELAJAR KETERAMPILAN SENAM LANTAI MELALUI PENDEKATAN MEDIA VIDIO VISUAL SISWA KELAS IPA1 SMA NEGERI 1 MERANGIN - Elya Roza, S.Pd., M.Pd (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The problems in this study are: the low learning outcomes of floor gymnastics skills in the material for front and back rolls for students of class X IPA 1 SMA Negeri 1 Merangin. The purpose of this study was to determine the extent to which learning outcomes can be improved through a visual video media approach for students of class X IPA 1 SMA Negeri 1 Merangin. This research method is classroom action research with the research subject is class X IPA 1 SMA Negeri 1 Merangin which consists of 32 students, with details of 21 female students and 11 male students. The research was conducted in two cycles of action. In the first and second cycles, an initial test of student performance was given, the teacher observed the students' activities in practicing during the training in teaching and learning activities, after watching a video show of the front roll and back roll floor gymnastics. The results of the evaluation and overall reflection in the first and second cycles. In the second cycle, the students' learning mastery results were 80.06% and the class average was 84.38%. And the success rate of the first cycle which only obtained learning completeness was 59.37% and the class average was 74.19%. The increase from the first cycle to the second cycle is 5.87 points. Based on the results of the evaluation and reflection of the second cycle, it is expected for Physical Education teachers at SMA Negeri 1 Merangin to use visual video media in learning floor gymnastics for the front roll and back roll for students. Because learning using audio-visual media helps teachers improve learning outcomes and make learning more interesting and varied.